The Impact of Gadget Use on Children's Emotional Development - Luluk Widi Astuti; Suryadi (STIT Attaqwa, 2025)
Technological advances are currently developing very quickly so that they have an impact on the lives of people, including children. Gadgets are one of the technologies that are currently very rampant, even early childhood is natural in using gadgets. The purpose of this study is to describe how the influence of gadget use on children's emotional development in Margototo Metro Kibang village. In this study, a qualitative method is used where the researcher obtains data based on observations, interviews, and documentation. As a result, researchers found that when children excessively use gadgets without parental control, they will tend to experience problems with their emotional development such as irritability, not being able to control themselves, and avoiding social interactions. Even so, if the use of gadgets in children can be limited and directed correctly by parents, gadgets can be useful as a learning medium. Therefore, parental involvement in the use of gadgets in children must actively monitor it so that children's emotional development continues to run well in the development of this technology.